Labview based data acquisition system for photoacoustic system - Teo, Bryan Soon Heng (2015)
Photoacoustic imaging has gained popularity and the use of computers to acquire and process the data very quickly and efficiently is essential. LabVIEW is a programming software which is visually interactive and is commonly used in the engineering industry. The following report is on the creation of a LabVIEW program that would be able to acquire and process the data from a photoacoustic imaging system. It will also synchronize several instruments and integrate the entire photoacoustic imaging system. The program would be specific to the GaGe data acquisition card.